2013
DOI: 10.1007/s11999-013-2822-0
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Gold Standard for TKA Tibial Component Rotational Alignment?

Abstract: Background Joint function and durability after TKA depends on many factors, but component alignment is particularly important. Although the transepicondylar axis is regarded as the gold standard for rotationally aligning the femoral component, various techniques exist for tibial component rotational alignment. The impact of this variability on joint kinematics and stability is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
2
35
1
Order By: Relevance
“…Several anatomic landmarks exist to align the tibial component, including the projected femoral TEA, medial border of the tibial tubercle, medial third of the tibial tubercle, and transverse axis of the tibia among others [13]. Our findings with regard to rotation are determined according to the line joining the medial third of the tibial tubercle and the PCL attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Several anatomic landmarks exist to align the tibial component, including the projected femoral TEA, medial border of the tibial tubercle, medial third of the tibial tubercle, and transverse axis of the tibia among others [13]. Our findings with regard to rotation are determined according to the line joining the medial third of the tibial tubercle and the PCL attachment.…”
Section: Discussionmentioning
confidence: 99%
“…In general, TKA produces a ‘looser’ knee over the native condition and allows more internal–external tibial rotation during passive flexion by 4.8 degrees 9. In addition to this phenomenon, some TKA designs (eg, mobile-bearing and rotating platforms) allow even more rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Hutter et al [18] recently concluded that given the large variability among 10 cadaveric knees, there is currently no gold standard for rotational alignment of the tibial component that can be recommended for use in all patients. Previous studies [7,20] also addressed the limitation of fixed anatomical landmarks in determining the correct tibial rotational setting during TKA.…”
Section: Discussionmentioning
confidence: 99%
“…After the MBTT is cleared of soft tissues, the point at which this line intersects the junction of the anterior and proximal surfaces of the tibia is marked using electrocautery. To overcome the limitation of the large variation induced using a fixed anatomical landmark [8,11,12,18,19], several authors have recommended a mobile-bearing design prosthesis that enables accommodation of tibiofemoral malrotation by a mobile tibial insert that self-aligns relative to the femoral component [7,8,12,19,20].…”
Section: Introductionmentioning
confidence: 99%